Fiber Volume Fraction Influence on Randomly Distributed Short Fiber Tungsten Fiber‐Reinforced Tungsten Composites. Issue 6 (29th March 2020) - Mao, Yiran; Coenen, Jan W.; Riesch, Johann; Sistla, Sree; Almanstötter, Jürgen; Terra, Alexis; Chen, Chang; Wu, Yucheng; Raumann, Leonard; Höschen, Till; Gietl, Hanns; Neu, Rudolf; et al.
Abstract : For future fusion reactors, tungsten (W) is currently the main candidate for the application as plasma‐facing material due to its several advanced properties. To overcome the brittleness of W, randomly distributed short W fiber‐reinforced W (Wf /W) composites have been developed using field‐assisted sintering technology (FAST). Herein, Wf /W materials with different fiber volume fraction (20–60%) are manufactured by FAST process to study the fiber volume fraction influence on the composite properties. Wf /W with ductile fibers and brittle fibers is produced using different tool setups during the production. Three‐point bending tests on prenotched samples, 4‐point bending tests, and tensile tests have been performed to determine the fracture behavior and flexural/tensile strength of the material. Wf /W materials with 30–40% fiber volume fraction exhibit a promising pseudoductile behavior, similar to fiber‐reinforced ceramic composites. However, Wf /W with 20% and >50% fiber volume fraction shows only a limited extrinsic toughening effect. In terms of flexural strength, with increasing fiber volume fraction, the tensile/flexural strength does not show a clear increasing tendency, or even lightly decreases. Abstract : Tungsten fiber‐reinforeced tungsten (Wf /W) with different fiber volume fraction (20–60%) is manufactured by field‐assisted sintering technology process to study the fiber volume fraction influence on the composite properties. Wf /W with ductile fibers and brittle fibers are produced using different tool setups. The results indicate that Wf /W materials with 30–40% fiber volume fraction exhibit a promising pseudoductile behavior.